Neighborhood disadvantage and preterm delivery in Urban African Americans: The moderating role of religious coping. (December 2016) - Sealy-Jefferson, Shawnita; Slaughter-Acey, Jaime; Caldwell, Cleopatra H.; Kwarteng, Jamila; Misra, Dawn P.
Abstract: Evidence suggests that neighborhood disadvantage predicts preterm delivery (PTD). However, the design of most existing studies precludes within-group analyses, which would allow the identification segments of the population at highest risk, as well as preventive factors. African Americans (AA) are disproportionately affected by PTD, are disproportionately concentrated in disadvantaged neighborhoods, and frequently use religious coping in response to chronic stressors. Our objective was to examine the association between neighborhood disadvantage and PTD, and whether religious coping moderated the associations, among postpartum AA women. Addresses from participants of the Life Influences on Fetal Environments Study (n=1387) were geocoded and linked to data from the American Community Survey. An index of neighborhood disadvantage was derived from a principal components analysis of the following variables: % below poverty, % unemployed, % receiving public assistance income, % college educated, % AA, % female-headed households, % owner occupied homes, median income, and median home value. Three domains of religious coping were assessed: organizational (church attendance), non-organizational (praying for self and asking others for prayer), and personal or subjective (experiences, perceptions, and sentiments about religion), and all were dichotomized as frequent/infrequent or satisfied/not satisfied. Preterm delivery was defined as birth before 37 completed weeks of gestation. Prevalence ratios and 95% confidence intervals were estimated with log binomial regression models. Neighborhood disadvantage did not predict PTD rates in the overall sample. However, there was evidence of moderation by asking others for prayer ( P for asking for prayer X disadvantage index interaction term: 0.01). Among women who infrequently asked others for prayer, neighborhood disadvantage was positively associated with PTD rates (adjusted Prevalence ratio: 1.28, 95% Confidence Interval: 1.01, 1.63), and a null association was found for those who frequently asked others for prayer. No evidence of moderation by the other religious coping variables was present. Non-organizational religious coping may buffer against the adverse effects of neighborhood disadvantage on PTD rates, among urban AA women. Future research should examine the mechanisms of the reported relationships. Highlights: We identified a novel preventive factor for preterm delivery in African Americans. Non-organizational religious coping may buffer against neighborhood disadvantage. Religiosity may provide health promoting social support for African American women.